The Effect of Bisoprolol on Heart Failure Preserved Ejection Fraction/HFpEF Patient’s Quality of Life - Ayu Asri Devi Adityawati; Anna Fuji Rahimah; Mohammad Saifur Rohman; Setyasih Anjarwani; Djanggan Sargowo (Heart Science Journal, 2021)
Global Publich Health Burden of Heart Failure reported the growing prevalence of heart failure from 26 million people affected in 2017 to 64.3 million affected in 2020 worldwide with half of the case classified as heart failure preserved ejection fraction/HFpEF. It is well known that someone who have been diagnosed with heart failure will have a poorer quality of life/QoL. β-blocker is a heart rate lowering agent with a potency to improve the patient’s clinical outcome. One clinical outcome that should always be evaluated and become the main goal of the therapy is QoL of the patient. This study aimed to observe and evaluate the effect of Bisoprolol, a type of β-blocker, in the improvement of HFpEF patient’s QoL. This study is a retrospective cohort following HFpEF patients who received β-blocker and HFpEF patients who did not received β-blocker in a span of 6 months. The study participant selected by purposive sampling method. Our study found that from all HFpEF patients who received β-blocker 86 patients had a good QoL, 16 patients had a Mod QoL, and 2 patients had a poor QoL (p=0.000). Mean physical score in the patient who did not received β-blocker was 13.84±11.01 while the mean score of the patient who received β-blocker was 5.94±4.95 (p=0.000). Mean emotional score in the patient who did not received β-blocker was 6.02±6.61 while the mean score of patient who received β-blocker was 1.83±2.16 (p=0.000). We conclude that the use of Bisoprolol could improve the HFpEF patient’s QoL evaluated by total score, physical score, and emotional score.